2011
DOI: 10.1097/jcn.0b013e318200ed94
|View full text |Cite
|
Sign up to set email alerts
|

Perceived Adverse Drug Events in Heart Failure

Abstract: Background: Patients with heart failure (HF) often perceive adverse drug events (ADEs), affecting quality of life. For weighing the benefits and burden of medication in HF care, knowledge on patients' perception of ADEs is needed. Our aim was to assess these ADE perceptions and to identify factors related to these perceptions. Methods: A cross-sectional study was performed including HF patients recruited from primary care and outpatient clinics. Patients were included in the analysis if they perceived an ADE i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 36 publications
1
2
0
Order By: Relevance
“…Results of this study are supported by a recent review by Bosworth and colleagues who reported that barriers are prominent and emphasized that low health literacy and poor communication were key components of poor adherence [84]. A larger study of both women and men found that 67% of 495 HF patients (38% female) reported adverse medication effects within the last month, averaging three adverse medication effects per patient [86]. Of these patients, 40% felt that these side effects could not be controlled, emphasizing the importance of communication about HF medications, adverse side effects and adherence.…”
Section: Hf and Medication Adherencesupporting
confidence: 73%
“…Results of this study are supported by a recent review by Bosworth and colleagues who reported that barriers are prominent and emphasized that low health literacy and poor communication were key components of poor adherence [84]. A larger study of both women and men found that 67% of 495 HF patients (38% female) reported adverse medication effects within the last month, averaging three adverse medication effects per patient [86]. Of these patients, 40% felt that these side effects could not be controlled, emphasizing the importance of communication about HF medications, adverse side effects and adherence.…”
Section: Hf and Medication Adherencesupporting
confidence: 73%
“…Similarly, Passik [ 97 ] asked participants undergoing cancer treatment about common treatment side effects, such as weight loss, constipation, nausea, pain, or vomiting. DeSmedt et al [ 88 ] asked heart failure patients about adverse drug events, without specifically discussing treatment burden. Eiser and Upton [ 89 ] aimed to provide estimates of the cost of caring for a child with cancer, without specifically discussing how the cost of treatment could be a critical dimension of treatment burden.…”
Section: Resultsmentioning
confidence: 99%
“…Frailty, prevalent in up to 75% of community-dwelling HFpatients 5 , can reduce the ability to tolerate adverse effects 6,7 . Up to 91% of HF-patients perceived their ADE as a chronic problem 8 . Persistent intolerance to HF-pharmacotherapy can impact quality of life (QoL) associated with 38% likelihood of dose changes or discontinuation 9 .…”
Section: Introductionmentioning
confidence: 99%